PERBANDINGAN SARI BENGKUANG DAN SARI DAUN PANDAN DALAM PEMBUATAN SIRUP - Eri Hernanda; Akhyar Ali; Vonny Setiaries Johan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Bengkuang was rich in nutrition, but so far the utilization of bengkuang was still less. Syrup was a way of product diversification of bengkuang. The purpose of this research was to get the best ratio of  bengkuang extract and pandanus leaf exctract in making syrup based on National Standard of Indonesian. This research used a Completed Randomized Design with five treatments and four replications. The treatments were ratio of bengkuang extract and pandanus leaf extract BP1 (100:0), BP2 (95:5), BP3 (90:10), BP4 (85:15), and BP5 (80:20). The value of observation were analyzed using Analysis of Varians followed by Duncan’s New Multiple Range Test on 5% level. The result of this research showed that ratio of  bengkuang extract and pandanus leaf extract given significantly effect on sucrose concentration, viscosity, colour, smell and overall hedonic assessment, but not significants on visibility and flavour. The best treatment was BP5 (80:20bengkuang extract and pandanus leaf extract) with sucrose concentration 71.63%, viscosity 451.46 cP, colourgreen, visibility not muddy, flavourfull pandanus, taste sweet and overallassesment favored by panelists. Keywords: Syrup, bengkuang extrac, pandanus leaf extract.